Structure of three tandem filamin domains reveals auto-inhibition of ligand binding. - Lad, Y; Kiema, T; Jiang, P; Pentikäinen, O; Coles, C; Campbell, I; Calderwood, D; Ylänne, J (2007)
Human filamins are large actin-crosslinking proteins composed of an N-terminal actin-binding domain followed by 24 Ig-like domains (IgFLNs), which interact with numerous transmembrane receptors and cytosolic signaling proteins. Here we report the 2.5 A resolution structure of a three-domain fragment of human filamin A (IgFLNa19-21). The structure reveals an unexpected domain arrangement, with IgFLNa20 partially unfolded bringing IgFLNa21 into close proximity to IgFLNa19. Notably the N-terminus of IgFLNa20 forms a beta-strand that associates with the CD face of IgFLNa21 and occupies the binding site for integrin adhesion receptors. Disruption of this IgFLNa20-IgFLNa21 interaction enhances filamin binding to integrin beta-tails. Structural and functional analysis of other IgFLN domains suggests that auto-inhibition by adjacent IgFLN domains may be a general mechanism controlling filamin-ligand interactions. This can explain the increased integrin binding of filamin splice variants and provides a mechanism by which ligand binding might impact filamin structure.